The Mediating Role of Perceived Stress in the Relationship Between Sleep Quality and Psychological Resilience with Emotional Eating in Students - Tork Zahrani, Parisa; kiamarsi, Azar; Zomorodi, Saeedeh (Mental Health and Lifestyle Journal, 2026)
The present study aimed to determine the mediating role of perceived stress in the relationship between sleep quality and psychological resilience with emotional eating in students. The research method was descriptive–correlational. The statistical population included all students of the Islamic Azad University, Rasht Branch, during the 2024–2025 academic year. A sample of 400 participants was selected through convenience sampling. Data were collected using the Salzburg Emotional Eating Scale (Meule et al., 2018), the Connor–Davidson Resilience Scale (Connor & Davidson, 2003), the Pittsburgh Sleep Quality Index (Buysse et al., 1989), and the Perceived Stress Scale (Cohen, 1983). The results showed that the indirect effect of sleep quality on emotional eating was −0.26, and the total effect of sleep quality on emotional eating was −0.276. Moreover, the indirect effect of psychological resilience on emotional eating was −0.29, while the total effect of psychological resilience on emotional eating was estimated at −0.282. The model also demonstrated a good fit. The findings highlight the importance of enhancing psychological resilience and improving sleep quality as effective strategies to reduce unhealthy behaviors such as emotional eating among students.